DESTINATION COMPETITIVENESS ON THE BASIS OF PSYCHOGRAPHIC TYPOLOGY OF TOURISTS (THE CASE OF NORTH SUMATRA) - Emrizal Emrizal; Wiendu Nuryanti; Budi Prayitno; Ahmad Sarwadi (Jurnal Ilmiah Hospitality Management, 2015)
Destination competitiveness is not always about comparison among competitors, but it also relates to what type of tourists (segment). Tourists’ psychographic type and their composition provide a strong indication of the status of a particular destination with regard to what segment is competitive. Using Plog’s long standing model of tourists psychographic tipology,  this study focuses on examining the psychographic position (competitiveness) of  North Sumatra as tourism destination. Qualitative and quantitative approaches are used in this research. A survey was conducted to foreign tourists for three months during the period of July 2013 to September 2013. This study found that North Sumatra is more competitive to allocentric group of tourists rather than psychocentric segments. Implication of this finding is discussed for planning purpose.